Prevalence Of Events And Reports Symptoms Of Computer Vision Syndrome (CVS) In Nursing Students In Indonesia During Virtual Face Learning Current Time Of The Covid-19 Pandemic - Rachman, Aulia; Oktovin, Oktovin (Jurnal EduHealth, 2022)
While undergoing the learning process during the Covid-19 pandemic, nursing students must deal with digital device screens such as computers, laptops, and smartphones that are connected to the internet for a long time and continuously. Continuous use of digital devices harms health, such as Computer Vision Syndrome (CVS). This condition causes sufferers to experience visual disturbances, eye muscle, and musculoskeletal disorders. This research aims to describe the prevalence of CVS events and symptoms felt by nursing students while undergoing virtual face-to-face lectures during the Covid-19 pandemic. This type of research is quantitative research with a descriptive approach. The sample of this research was 494 students from 13 public and private universities in Indonesia. This sample was selected with the Cluster Sampling Technique. The results of this study showed that the majority of nursing students complained of headaches with moderate complaints (80.2%), eye fatigue with moderate complaints (75.9%), eye redness with mild complaints (50.0%), blurred vision with complaints moderate (49.2%), dry eyes with mild complaints (74.5%), pain in the shoulders and neck with moderate complaints (40.1%). The majority of the time, using digital devices (laptops, computers, or smartphones) in attending online lectures ≥5 hours (98.6%). Most device screen monitor lighting is bright (78.7%), and the position when using most devices is in the wrong category (87.0%). Most CVS complaints among nursing students from various regions in Indonesia are at a moderate level related to complaints of headaches, eye fatigue, redness, blurred vision, and shoulder and neck pain. This can be attributed to using electronic devices for more than 5 hours in one day and poor behaviour when using these devices